Utility of autologous fecal microbiota transplantation and elucidation of microbiota in diversion colitis. Issue 1 (31st October 2021) - Tominaga, Kentaro; Tsuchiya, Atsunori; Mizusawa, Takeshi; Matsumoto, Asami; Minemura, Ayaka; Oka, Kentaro; Takahashi, Motomichi; Yoshida, Tomoaki; Kojima, Yuichi; Ogawa, Kohei; Kawata, Yuzo; Nakajima, Nao; et al.
Abstract: Objectives: Diversion colitis (DC) is an inflammatory disorder caused by interruption of the fecal stream and subsequent nutrient deficiency from luminal bacteria. The utility of fecal microbiota transplantation (FMT) for DC was recently investigated; however, the precise pathogenesis of this condition remains unclear. This study aimed to evaluate the utility of autologous FMT in DC and to determine the related changes in the intestinal microbiota. Methods: Autologous FMT was performed to reestablish the intestinal microbiota in five patients (average age, 64.6 ± 8.3 years) with DC. They underwent double‐ended colostomy. We assessed the diverted colon by endoscopy and evaluated the microbiota before and after FMT using the 16S rRNA gene sequencing method. Results: All five patients had mild inflammation (ulcerative colitis endoscopic index of severity [UCEIS] 2–3) in the diverted colon based on the colonoscopic findings. Three patients presented with symptoms, such as tenesmus, mucoid stool, and bloody stool. With FMT treatment, all patients achieved endoscopic remission (UCEIS score of 0 or 1) and symptomatic improvement. We observed a significantly decreased α‐diversity in DC patients compared to healthy controls. The frequency of aerobic bacteria, such as Enterobacteriaceae, in the diverted colon decreased after autologous FMT. Conclusions: This study was the first to show that the microbiota in the diverted colon was significantly affected by autologous FMT. Since interruption of the fecal stream is central to the development of DC, FMT can be considered a promising treatment.